CLASSIFICATION OF SCIENCES AND SCIENTIFIC HERITAGE OF ABU (Conference Zone, 2022)
The article scientifically analyzed the scientific heritage and classification of sciences of the great Khorezmian scientist Abu Abdullah al-Khwarizmi. The main work in the field of classification of sciences is "Mafatih al-ulum" (mfatih al-alvm) ("The Key of Sciences"), an encyclopedic work that provides information about the science and culture of the Muslim countries of the East in its time, and contains almost all scientific fields of that time: jurisprudence, philosophy, logic, poetry. , including calculus, geometry, chemistry, and more. The article scientifically substantiates the lunar scientific heritage of Abu Abdullah al-Khwarizmi and his main contributions to science.